PWE-181 Pancreatic exocrine function after major upper gastrointestinal surgery measured with a carbon 13 mixed triglyceride breath test. (28th May 2012) - Ward, S; Cade, R; Mackay, S; Hassen, S; Banting, S; Gibson, P
Abstract : Introduction: Major upper gastrointestinal resectional surgery, including oesophagectomy, gastrectomy and pancreatico-duodenectomy, can result in post-operative nutritional difficulties, which may in part be associated with reduced pancreatic exocrine function, but there is debate in the literature about the actual proportion of these patients that have pancreatic exocrine insufficiency which may then benefit from oral supplementation. The Carbon 13 labelled mixed triglyceride breath test (C13-MTG-BT) was used to indirectly measure pancreatic exocrine function in post-operative patients and these results were compared to the test performed in control subjects. Methods: 30 normal subjects, 15 post-oesophagectomy patients, 15 post-gastrectomy patients and 10 post-pancreatico-duodenectomy patients were recruited to undertake the C13-MTG-BT at Box Hill Hospital, Melbourne, Australia, between August 2009 and January 2011. The C13-MTG-BT was performed using 200 mg of C13-MTG substrate and measured using an infra-red isotope spectrometer. The cumulative percentage of ingested C13 exhaled after 6 h and the time at peak rate of C13 excretion were measured in all subjects and compared between groups, with statistical significance calculated using the Student t test. Results: The mean cumulative percentage of ingested C13 exhaled after 6 h in the control group was 28.6% with a SD of 8.8%. The cumulative percentage exhaled after 6 h in each post-operative group compared with the control group was not significantly different. The time of peak rate of C13 excretion was earlier in the post-operative groups compared with the control group. Conclusion: This study has not found a large percentage of patients post major upper gastrointestinal resections with measurable reduction in pancreatic exocrine function using the C13-MTG-BT, which is in contrast to the literature. The finding of earlier times of peak rate of excretion imply the post-operative patients tend to have more rapid gut transit. Larger and prospective studies using this test or another pancreatic function test may be useful to detect the proportion of post-operative patients with pancreatic exocrine insufficiency that may then benefit from pancreatic exocrine supplementation. Competing interests: None declared.